THE REFLECTION OF THE HUMAN IMAGE THROUGH ZOONYMIC PHRASEOLOGICAL UNITS IN THE ENGLISH AND UZBEK LANGUAGES (Eureka Journal of Language, Culture & Social Change, 2026)
This study explores the linguistic manifestation of human characteristics through zoonymic phraseological units (ZPUs) – idiomatic expressions involving animal names – in English and Uzbek. By employing a comparative-typological analysis, the research identifies how different cultures project human traits, social behaviors, and physical appearances onto the animal kingdom. The findings reveal that while both languages share universal metaphors such as, the “brave lion” or “stubborn donkey”, they diverge significantly based on historical lifestyle and religious influences. This article highlights the anthropocentric nature of language and the role of “animal-metaphor” in shaping national-cultural identities.
Keywords: Zoonymic phraseology, comparative linguistics, English language, Uzbek language, linguaculture, anthropocentrism, animal metaphors.